Technetium (Tc)/Rhenium (Re) solubility and leaching behavior from waste forms: An overview - Singh, Bhupendra Kumar; Kim, Jueun; Pak, Donghun; Kim, Kyungwon; Um, Wooyong (Frontiers in Nuclear Engineering, 2023)
Technetium-99 (99Tc), a radionuclide generated from nuclear industry is a great environmental concern because of its long half-life (2.13 × 105 years) and high mobility in environment. Therefore, apposite management of 99Tc is imperative to control its hazardous radiological impact on humans and other livings. So far, the major strategy implementation has been the solidification and immobilization of 99Tc radioactive waste in various matrices as waste forms and disposal in deep geological repository. However, by passing the time, 99Tc may leach out/solubilize from the waste forms under different geochemical/environmental conditions. In this minireview, we discuss some key contributions towards the solubility of 99Tc and rhenium (Re; a well-known surrogate of 99Tc) from different waste forms. Specifically, we review the solubility of 99Tc from glass, cement, ceramic, and geopolymer waste forms. The final section (conclusion) presents a short summary and future challenges need be addressed to impede the solubility of 99Tc from the designed waste forms. We believe this minireview will be beneficial to provide a significant insight on the solubility of 99Tc from aforementioned waste forms and in the design of robust matrices to minimize/prevent 99Tc migration in various environments.